Interleukin‑6 Contributes to the Paracrine Effects of Cardiospheres Cultured from Human, Murine and Rat Hearts. Issue 11 (November 2014) - Maxeiner, Hagen; Mufti, Solaiman; Krehbiehl, Nina; Dülfer, Friederike; Helmig, Simone; Schneider, Joachim; Böning, Andreas; Matejec, Reginald; Weigand, Markus A.; Schlüter, Klaus‐Dieter; Wenzel, Sibylle
Abstract Cardiosphere‐derived cells (CDCs) were cultured from human, murine, and rat hearts. Diluted supernatant (conditioned‐medium) of the cultures improved the contractile behavior of isolated rat cardiomyocytes (CMCs). This effect is mediated by the paracrine release of cytokines. The present study tested the hypothesis, that the cardiovascular state of the donor's heart influences this effect on CMCs and tries to identify the responsible factors. CDCs were cultured from human tissue samples of cardiac surgery and from murine and rat hearts. The supernatants of cultured CDCs from hypertensive humans and rats showed a higher improvement of the contractile behavior of CMCs compared to CDCs of normotensive origin. Subsequently, the cytokine profile of the supernatants was analyzed. Among the cytokines elevated in supernatants originating from hypertensive humans or rats was Interleukin‑6. CDCs were also generated from Interleukin‑6−/−‐mice and their wildtype littermates. The supernatant of the cultured Interleukin‑6−/−‐CDCs had no effect on the contractile behavior, whereas the supernatant of the Interleukin‑6+/+‐CDCs showed a positive effect. To confirm the hypothesis that Interleukin‑6 contributes to the paracrine effects, CMCs were incubated with Interleukin‑6. It improved the contractile function in a concentration dependent way. Finally, the effect of the supernatant of cultured CDCs derived from a hypertensive human sample could be abolished by simultaneous incubation with a specific Interleukin‑6 antibody. CDCs release cytokines that improve the contractile behavior of CMCs. This effect is more intense in CDCs from hypertensive donors. Interleukin‑6 is involved in this phenomenon. J. Cell. Physiol. 229: 1681–1689, 2014. © 2014 Wiley Periodicals, Inc.